TOWARD AN ADAB-BASED CONCEPTUAL CHARACTER EDUCATION MODEL: INTEGRATING LICKONA AND AL-ATTAS IN PROJECT-BASED LEARNING FOR ISLAMIC ELEMENTARY SCHOOLS - Parina, Parina; Syihabuddin, Syihabuddin; Somad, Momod Abdul; Kosasih, Aceng (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
Background: Character education in Islamic schools faces the challenge of integrating universal moral values with spiritual principles derived from Islamic teachings. However, many existing character education models tend to separate Western moral frameworks from Islamic epistemological foundations, particularly the concept of adab as the core of holistic human formation. Purpose: This study aims to develop a conceptual character education model through the integration of Thomas Lickona’s character education framework and Syed Muhammad Naquib al-Attas’s concept of adab within the context of Project-Based Learning (PBL) in Islamic elementary schools. Method: The research employs a library research approach using thematic analysis and conceptual synthesis of relevant primary and secondary literature. Result: The findings indicate that Lickona’s three dimensions of character education—moral knowing, moral feeling, and moral action—can be harmonized with the principles of knowledge (‘ilm), adab, and righteous action (‘amal) in Al-Attas’s thought to construct a comprehensive Islamic character education model. This integration strengthens the spiritual and epistemological foundations of character education while providing a systematic pedagogical structure through PBL, which emphasizes reflective, collaborative, and contextual learning. Implication: This study offers a novel conceptual framework that positions adabas the ontological foundation of character education within project-based pedagogy. The proposed model also provides practical implications for curriculum design and instructional planning in Islamic elementary education.